2005
DOI: 10.1007/bf03168982
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory function in people with genetic risk of dementia

Abstract: Further investigation is required to explore the reasons for the higher prevalence of olfactory dysfunction in epsilon-4 allele positive subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 35 publications
1
1
0
Order By: Relevance
“…Despite the absence of a significant interaction with sex and APOE ε4 allele, the estimates and direction of risk were consistent with studies reporting stronger associations of impaired olfaction with cognitive impairment in APOE ε4 allele carriers than non-carriers. 4,16,48,49 Consistent with the present study, however, another study did not find a significant interaction of B-SIT score with APOE genotype. 5 …”
Section: Discussionsupporting
confidence: 91%
“…Despite the absence of a significant interaction with sex and APOE ε4 allele, the estimates and direction of risk were consistent with studies reporting stronger associations of impaired olfaction with cognitive impairment in APOE ε4 allele carriers than non-carriers. 4,16,48,49 Consistent with the present study, however, another study did not find a significant interaction of B-SIT score with APOE genotype. 5 …”
Section: Discussionsupporting
confidence: 91%
“…It has long been recognized that olfaction is impaired in persons with clinically diagnosed AD 22–27 . Olfactory function is also impaired in MCI, 26–31 a precursor of AD, and in those with at least one copy of the apolipoprotein E ɛ4 allele, 28,32–34 a well established risk factor for AD. In previous research in this cohort, we showed that odor recognition performance predicted incidence of MCI and AD, rate of cognitive decline, and level of AD pathology on postmortem examination 4,5 .…”
Section: Discussionmentioning
confidence: 99%